O processo de ensino-aprendizagem: as significações dos estudantes em um Projeto de Atendimento Psicopedagógico Institucional de uma escola municipal no interior paulista - Rosa, Cristiane de Morais (2023)
This study aimed to investigate the teaching-learning process in one of its dimensions: the meanings of the students of an Institutional Psychopedagogical Assistance Project (API) at a municipal school in the interior of São Paulo State. This is qualitative study whose research subjects were two students in the final years of Elementary School who were and continue to be assisted in the aforementioned project. For the required information to compose the data, we used semi-structured interviews with the participating students (a male and a female student from the API Project) who remained in the Project in the year the research was carried out, in addition to documents that regulate the service offered by the Project (CME 02/2014) and its aspects regarding the subjects, highlighting the reasons for referring students to the Project. The theoretical framework of Socio-historical Psychology was applied, and the meanings constituted by the collaborating subjects about their teaching-learning process at school were investigated, highlighting learning difficulties, facilities and assistance, the reasons for their referral to the Project and coping with the pandemic period. The core meaning analysis procedure was used based on Aguiar and Ozella (2013), presenting significant elements related to the teaching-learning process, with emphasis on the tensions and suffering experienced by the students in the schooling process; meanings regarding what it means to be a good student; and highlighting activities they carry out to become good students